2010
DOI: 10.1111/j.1540-6261.2010.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Information and Incentives Inside the Firm: Evidence from Loan Officer Rotation

Abstract: We present evidence that reassigning tasks among agents can alleviate moral hazard in communication. A rotation policy that routinely reassigns loan officers to borrowers of a commercial bank affects the officers' reporting behavior. When an officer anticipates rotation, reports are more accurate and contain more bad news about the borrower's repayment prospects. As a result, the rotation policy makes bank lending decisions more sensitive to officer reports. The threat of rotation improves communication becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
129
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(131 citation statements)
references
References 53 publications
(58 reference statements)
2
129
0
Order By: Relevance
“…For example, "a fads-and-fashions effect can influence loan officers who may prefer to lend to firms in exciting or innovative industries even if industry performance indicators suggest otherwise" (McNamara & Bromiley, 1997, p. 1070. Hertzberg, Liberti, and Paravisini (2010) showed empirically that loan officers might have an information bias and strong risk aversion. Using data from a large multinational U.S. bank operating in Argentina, they concluded that loan officer, who is responsible for forecasting the borrower's creditworthiness and reporting information about them, reveals negative information about their borrowers' repayment prospects because of the threat of job rotation.…”
Section: Loan Officers' Subjective Judgment: Noise or New Informationmentioning
confidence: 99%
“…For example, "a fads-and-fashions effect can influence loan officers who may prefer to lend to firms in exciting or innovative industries even if industry performance indicators suggest otherwise" (McNamara & Bromiley, 1997, p. 1070. Hertzberg, Liberti, and Paravisini (2010) showed empirically that loan officers might have an information bias and strong risk aversion. Using data from a large multinational U.S. bank operating in Argentina, they concluded that loan officer, who is responsible for forecasting the borrower's creditworthiness and reporting information about them, reveals negative information about their borrowers' repayment prospects because of the threat of job rotation.…”
Section: Loan Officers' Subjective Judgment: Noise or New Informationmentioning
confidence: 99%
“…In many banks in Japan, loan officers rotate (i.e., transfer from one branch to another) every 2–5 years, which is driven by regulatory guidance (Uchida, Udell, and Yamori ). In a large multinational bank in Argentina, turnover is made within 3 years (Hertzberg, Liberti, and Paravisini ).…”
mentioning
confidence: 99%
“…It can reduce credit availability for small firms (Scott, ). However, Hertzberg, Liberti, and Paravisini () do not share the same opinion: Studying the Argentinian branch of a large multinational American bank where a 3‐year rotation rule was applied for loan officers, the authors showed that this rotation policy may improve transfer of information within the bank. Indeed, when loan officers fear to be rotated, they will be more inclined to disclose bad news about the creditworthiness of their clients because they do not want their substitutes to do it themselves.…”
Section: Literature Reviewmentioning
confidence: 99%